Digital Based Guided Note Taking Toward Preservice Elementary Teacher Retention on Science - Taufik, Leo Muhammad; Novianawati, Noor (International Conference on Elementary Education, 2020)
The potential of making digital notes has been reported by number of study. However the quantity of digital based notes cannot guarantee its quality. Therefore further testing is needed to determine quality of digital notes taking on student retention. The study was carried out to investigate of the digital based guided note taking preservice elementary teacher retention on basic concept of science class. This study employs quasy-experiment method by using pretest-posttest control group design. Two classes of students participated in this study – control class was taught by power point and take notes by traditional notes taking; the experiment class was taught by power point and take notes by digital based guided note taking. Retention was measured three weeks after final examination. The result suggest that digital based guided note taking improve student retention with the categories. The graphical data with standard statistical analyses (t-test) show that retention between control and experiment class was not different